2014
DOI: 10.1074/jbc.m114.554659
|View full text |Cite
|
Sign up to set email alerts
|

Assembly Mechanism of Trypanosoma brucei BILBO1, a Multidomain Cytoskeletal Protein

Abstract: Background: TbBILBO1 is the only known protein component of the flagellar pocket collar, but its assembly remains unknown. Results: Structural dissections of the three different domains of TbBILBO1 revealed their roles in protein assembly. Conclusion: TbBILBO1 forms a linear filament that interacts laterally to form a fibrous bundle. Significance: The data show how two types of coiled coil act together to assemble TbBILBO1 into long filaments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(45 citation statements)
references
References 41 publications
2
43
0
Order By: Relevance
“…Using electron microscopy Vidilaseris et al , demonstrated that the EF-hand domains of BILBO1 change their conformation upon calcium binding, and the coiled-coil domain can form anti-parallel dimers, which can then form linear polymers via the C-terminal leucine zipper. Further, they demonstrated that these filaments can condense into fibers through lateral interactions [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using electron microscopy Vidilaseris et al , demonstrated that the EF-hand domains of BILBO1 change their conformation upon calcium binding, and the coiled-coil domain can form anti-parallel dimers, which can then form linear polymers via the C-terminal leucine zipper. Further, they demonstrated that these filaments can condense into fibers through lateral interactions [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The primary and secondary structures of BILBO1 do not predict a specific function, and the protein does not appear to have any obvious membrane-targeting domains, but it does possess two predicted EF-hand calcium-binding domains (aa 185–213 and aa 221–249). It also has a large coiled-coil (CC) domain (aa 263–566), which is involved in protein-protein interactions [ 15 ]. Based on our hypothesis that BILBO1 is the FPC scaffold, we decided to determine 1) if BILBO1 can form polymers in vivo , 2) what domain(s) of the protein is(are) involved in polymer formation.…”
Section: Introductionmentioning
confidence: 99%
“…Of these, the best characterized is an electrondense horseshoe-shaped structure named the flagellar pocket collar (FPC) (4). The only known component of the FPC is the protein TbBILBO1, which has been localized to the FPC by immunoelectron microscopy (immuno-EM) and shown to be essential for FP biogenesis (9)(10)(11)(12).…”
mentioning
confidence: 99%
“…TbBILBO1 was the first reported protein component of the FPC (5). It consists of four structural domains: a globular N-terminal domain; two central EF-hand motifs; a long coiled-coil domain; a C-terminal leucine zipper (6). Analysis using electron microscopy showed that TbBILBO1 forms long filaments in vitro (6,7).…”
Section: Instroductionmentioning
confidence: 99%
“…It consists of four structural domains: a globular N-terminal domain; two central EF-hand motifs; a long coiled-coil domain; a C-terminal leucine zipper (6). Analysis using electron microscopy showed that TbBILBO1 forms long filaments in vitro (6,7). Based on its modular architecture and intrinsic property to form spiral-like structures when ectopically expressed in vivo, TbBILBO1 was proposed to act as the structural core to recruit other components during FPC assembly (8,9).…”
Section: Instroductionmentioning
confidence: 99%